2022
DOI: 10.2991/absr.k.220305.024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Media on Nutritional Content of Black Soldier Fly (BSF) Larva in SITTI Technology System (Integration System – Plant – Livestock – Fish)

Abstract: Maggot is known to be able to become a bioconversion agent with three by-products, including the main product is Black Soldier Fly (BSF) larvae which can be used as animal feed because it contains protein. The second product is liquid from larval activity which can be used as liquid fertilizer. The last product is dry organic waste which can be used for plant fertilizer. Based on several explanations, research can be carried out on the feed media given to BSF maggots from various organic wastes. The media used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
1
Order By: Relevance
“…These findings align with previous research by Logan et al [7], who reported similar positive effects when incorporating chicken meat and egg wastes into chicken manure, thereby promoting BSF larvae development. Widyaswara et al [13] also reported improvements in BSF larvae development by adding organic household waste into chicken manure. Moreover, Schreven et al [14] also noticed that supplementation of camelina oilseed press cake into chicken manure could improve BSF larvae development.…”
Section: Resultsmentioning
confidence: 99%
“…These findings align with previous research by Logan et al [7], who reported similar positive effects when incorporating chicken meat and egg wastes into chicken manure, thereby promoting BSF larvae development. Widyaswara et al [13] also reported improvements in BSF larvae development by adding organic household waste into chicken manure. Moreover, Schreven et al [14] also noticed that supplementation of camelina oilseed press cake into chicken manure could improve BSF larvae development.…”
Section: Resultsmentioning
confidence: 99%
“…Makanan yang dicerna oleh BSF saat periode larva memengaruhi fisiologi, status nutrisi, perkembangan morfologi, dan sukses reproduksi saat dewasa (Gobbi et al 2013). Ketersediaan stok populasi BSF pada sistem pengelolaan limbah organik yang berkelanjutan sangat bergantung pada kemampuan reproduksi dan tingkat fekunditas BSF (Wicker-Thomas 2007). Reproduksi merupakan tahapan yang paling esensial dalam pengembangan dan pemeliharaan BSF secara efisien (Hoc et al 2019).…”
unclassified